Pengaruh Reputasi, Electronic Word of Mouth dan Web Quality Terhadap Kepercayaan Pelanggan Shopee di Kota Padang - Zuyyina Rahma Zalni; Abror Abror (Universitas Negeri Padang, 2019)
This study analyzes: (1) The effect of reputation on trust, (2) The effect of electronic word of mouth (ewom) on trust, (3) The effect ofweb quality on trust. This type of research is causative research. The population in this study is customers of Sopee in Padang city. By using purposive sampling, we use 196 customers as the respondent. This study used onlinequestionaires as the data collection instrument, this study analyzed the data by using multiple linear regression (MLR) with SPSS 21 as the software package. The results of this study indicate that: (1) reputation has a significant effect on trust (2) electronic word of mouth (ewom) has a significant effect on trust (3) web quality has a significant effect on trust. Keywords: reputation, electronic word of mouth, web quality, Trust